Ecology of Indigenous Lactic Acid Bacteria along Different Winemaking Processes of Tempranillo Red Wine from La Rioja (Spain) - Lucía González-Arenzana; Pilar Santamaría; Rosa López; Carmen Tenorio; Isabel López-Alfaro (The Scientific World Journal)
Ecology of the lactic acid bacteria (LAB) during alcoholic fermentation (AF) and spontaneous malolactic fermentation (MLF) of Tempranillo wines from four wineries of La Rioja has been studied analyzing the influence of the winemaking method, processing conditions, and geographical origin. Five different LAB species were isolated during AF, while, during MLF, only Oenococcus oeni was detected. Although the clonal diversity of O. oeni strains was moderate, mixed populations were observed, becoming at least one strain with distinct PFGE profile the main responsible for MLF. Neither the winemaking method nor the cellar situation was correlated with the LAB diversity. However, processing conditions influenced the total number of isolates and the percentage of each isolated species and strains. The winemaking method could cause that genotypes found in semicarbonic maceration did not appear in other wineries. Four genotypes of O. oeni were isolated in more than one of the rest wineries. These four together with other dominant strains might be included in a future selection process.